Peran, Kedudukan dan Tanggung Jawab Anak Tunggu Tubang pada Masyarakat Adat Semende di Kabupaten Muara Enim - Yogi Vitagora (Lembaga Pengembangan Kinerja Dosen, 2025)
The development of the role and position of the Tunggu Tubang child in the Mayorat inheritance system in the Semende customary law community in Muara Enim Regency, South Sumatra, this is influenced by factors such as education, migration, lifestyle changes, and religion such as working outside the village and hiring people to manage agricultural land, without violating customary provisions that are oral and inherited from generation to generation. The responsibility of the Tunggu Tubang children in resolving inheritance disputes in the majority inheritance system in the Semende indigenous people involves an important role in providing an understanding of the provisions of the Semende customary inheritance to the members of the Tunggu Tubang family, responsible for conducting deliberations with Payung Meraje in order to reach an absolute and binding decision.